The Jamaah Tabligh Movement in Indonesia: Peaceful Fundamentalist - Abdul Aziz (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
The birth of Jamaah Tabligh was in fact a direct reaction to the emergence of aggressive Hindu proselytization movement, such as the Shuddhi (Purifying) and Sangathan (Consolidation) movement, which made wide-reaching attempt in the early 20th century to